2014
DOI: 10.1186/s40490-014-0007-6
|View full text |Cite
|
Sign up to set email alerts
|

Decline in vitality of propagules of Phytophthora pluvialis and Phytophthora kernoviae and their inability to contaminate or colonise bark and sapwood in Pinus radiata export log simulation studies

Abstract: Background: Phytophthora pluvialis Reeser, W.L. Sutton & E.M. Hansen is the cause of a newly described disease, red needle cast, in certain stands of Pinus radiata D. Don in New Zealand that experience periodic foliage browning, while Phytophthora kernoviae Brasier, Beales & Kirk is also infrequently isolated from symptomatic needles. Methods: Studies were undertaken to test the possibility that these species may be transported on pine logs either as superficial contaminants or as colonists of bark or wood.Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…Field-based observations have indicated that the pathogen infects only the needle blade with shed needles, rain splash and air movement being the most likely drivers of pathogen movement. The potential for subsequent spread of the pathogen through the trade of export logs has been demonstrated to be negligible (Hood et al 2014). These findings are consistent to those made for Phytophthora pinifolia on Pinus radiata by Ahumada et al (2012) who similarly concluded that there was no evidence of pathogens surviving on sawn green timber.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Field-based observations have indicated that the pathogen infects only the needle blade with shed needles, rain splash and air movement being the most likely drivers of pathogen movement. The potential for subsequent spread of the pathogen through the trade of export logs has been demonstrated to be negligible (Hood et al 2014). These findings are consistent to those made for Phytophthora pinifolia on Pinus radiata by Ahumada et al (2012) who similarly concluded that there was no evidence of pathogens surviving on sawn green timber.…”
Section: Discussionsupporting
confidence: 81%
“…Re-isolation confirmed that Phytophthora pluvialis is the cause of red needle cast in Pinus radiata. Sampling by pathologists targeting fresh lesion material resulted in the isolation of Phytophthora from 76% of characteristic needle lesions (Hood et al 2014). Recovery of P. pluvialis from symptomatic needles was variable between collections but clearly decreased with time after infection had occurred.…”
Section: Discussionmentioning
confidence: 99%
“…Red needle cast (RNC) is a new needle disease caused by Phytophthora pluvialis Reeser, Sutton & E Hansen that causes defoliation of Pinus radiata D. Don (radiata pine) under conditions favourable to the development of the disease Hansen et al 2012;Hood et al 2014;Reeser et al 2013). The disease has become well established in certain areas of New Zealand and has the potential to cause production loss through needle shed and reduced growth.…”
Section: Introductionmentioning
confidence: 99%
“…Phytophthora pluvialis is a foliar pathogen isolated from needles of Pinus radiata, and sporangia that produce zoospores have been observed on needles under laboratory and field conditions. Extensive attempts to isolate or recover Phytophthora pluvialis from other plant tissues have been unsuccessful (Hood et al 2014). Likewise attempts to artificially colonise plant material other than needles have been unsuccessful.…”
Section: Impact and Risk Assessmentsmentioning
confidence: 99%
“…Likewise attempts to artificially colonise plant material other than needles have been unsuccessful. These findings, in conjunction with studies of spore survival on logs at different temperatures over time, have been used for risk assessments (Hood et al 2014). From a market access perspective, the possibility of transmitting Phytophthora pluvialis from New Zealand on radiata pine logs is negligible.…”
Section: Impact and Risk Assessmentsmentioning
confidence: 99%